(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2010)
The article deals with Ukrainian surnames, their distinctive phonetic, word-building, lexical features. The motivational relations between derivative base and anthroponomy are established. Emphasis is laid on the patronymic surnames and family names associated with professional activities. The ways of Ukrainian surname denationalization are identified.